Quran Memorisation And Heart Rate Variability: How Do They Correlate? - Ahmad Rohi Ghazali; Nor Malia Abd Warif; Noor Anisah A Yazit; Norsham Juliana Nordin; Ismarulyusda Ishak; Farah Wahida Ibrahim; Arimi Fitri Mat Ludin; Dzalani Harun; Santibuana Abd Rahman; Wan Nor Atikah Che Wan Mohd Rozali (BAISHIDENG PUBLISHING GROUP INC, 2024)
Non-Indexed Publication